RICKETS - Sotvoldiyeva Nilufar Xabibulla qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:This article discusses rickets, a childhood bone disease primarily caused  by  vitamin  D  deficiency,  which  leads  to  soft  and  weak  bones.  The  article outlines the main causes, including lack of sunlight, poor nutrition, and certain medical conditions that affect nutrient absorption. It also highlights the  common symptoms such as delayed growth, skeletal deformities, and muscle weakness. Diagnosis methods like blood tests and X-rays are described, along with effective strategies for prevention through sunlight exposure, balanced diet, and supplementation. The article concludes by  emphasizing that rickets is  both preventable  and  treatable with  proper care and nutrition.